2018
DOI: 10.3390/app8091668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Economic Indicators on the Integrated Design of Wind Turbine Systems

Abstract: This article presents a framework to integrate and optimize the design of large-scale wind turbines. Annual energy production, load analysis, the structural design of components and the wind farm operation model are coupled to perform a system-level nonlinear optimization. As well as the commonly used design objective levelized cost of energy (LCoE), key metrics of engineering economics such as net present value (NPV), internal rate of return (IRR) and the discounted payback time (DPT) are calculated and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous AWE literature includes LCOE estimation for a ground-gen farm vs. the number of units in the farm and the system scale [16], as well as estimating AWE system LCOE in order to compare to the best available renewable alternatives onshore [17] and to compare to other options for microgrids [18]. LCOE optimization for traditional wind turbines has been performed, to optimize blade length and hub height for systems in low wind speed areas using particle swarm optimization [19], to optimize rotor radius and rated speed for offshore systems [20], and to optimize rotor radius and rated speed for several wind conditions using a genetic algorithm [21].…”
Section: Airborne Wind Energymentioning
confidence: 99%
“…Previous AWE literature includes LCOE estimation for a ground-gen farm vs. the number of units in the farm and the system scale [16], as well as estimating AWE system LCOE in order to compare to the best available renewable alternatives onshore [17] and to compare to other options for microgrids [18]. LCOE optimization for traditional wind turbines has been performed, to optimize blade length and hub height for systems in low wind speed areas using particle swarm optimization [19], to optimize rotor radius and rated speed for offshore systems [20], and to optimize rotor radius and rated speed for several wind conditions using a genetic algorithm [21].…”
Section: Airborne Wind Energymentioning
confidence: 99%
“…There are also 4 papers dealing with wind turbine design. Wu et al [11] presented a framework to optimize the design of large-scale wind turbines by using different design objectives, such as levelized cost of energy, net present value, internal rate of return, and discounted payback time, and found that the blade obtained with economic optimization objectives has a much large relative thickness and smaller chord distributions than obtained with high aerodynamic performance design. Yang et al [12] investigated the design of wind turbine in low wind speed areas by considering both blade length and hub height.…”
Section: Current Status In Wind Turbine Aerodynamicsmentioning
confidence: 99%